Role of the chancre in development of immunity to tsetse-transmitted trypanosoma (Nannomonas) congolense in goats - Taiwo, V.O. (University of Ibadan, 1987)
Local skin reactions (chancres) developed in goats at the sites of deposition, by tsetse flies, ofLocal skin reactions (chancres) developed in goats at the sites of deposition, by tsetse flies, of metacyclics of Trypanosoma congolense. The chancres developed much faster and were more pronounced when ten infected tsetse were allowed to feed on a spot as compared to only one fly per spot. The initial host cellular reaction in the chancre was predominantly polymorphonuclear, followed at the peak of development of the chancre by a predominantly lymphoblastic and plasmacyticreaction. Trypanosomes were found in various stages of division as well as degeneration in chancre biopsies taken at various days post-infection (pj.). Most of the trypanosomes recovered from the chancre tissue fluid were found to bear the same variable surface glycoprotein (VSG) epitopes as the corresponding metacyclics for as long as 13 days p.i., as revealed by indirect immunofluorescence using mouse anti-metacyclic VSG hyperimmune sera and monoclonal antibodies. Immunization of goats with metacyclic trypanosomes, by exposure to infected tsetse bites followed by treatment of the infected goats on day 13 p.i., gave rise to the development of protection to homologous tsetse-transmitted challenge, whilst immunization by intravenous inoculation of the metacyclics did not induce such protection. Chancre formation would thus appear to be vital for the induction of comprehensive immune recognition of the metacyclic variable antigen repertoire deposited in the skin by infected tsetse, and hence development of protective immunity.